TINGKAT PENGETAHUAN REMAJA PUTRI KELAS III SMP TENTANG MENARCHE - Eva Nirwana BR Hutabarat (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2021)
Menarche is the first menstruation, the first menstrual cycle or the first menstrual bleeding in women. From a social and medical point of view, this condition is seen as an important event of female puberty, as a sign of fertility. Adolescents who have known about menarche will feel happy when they experience it. While negative feelings such as anxiety, fear, shame and confusion. This study aims to determine the level of knowledge of young women about menarche at SMP St.Yoseph Medan. This research method is descriptive research. The number of samples as many as 53 people, sampling using total sampling technique. From 53 respondents, the results showed that the majority of respondents' knowledge about menarche was in the sufficient category, which was 50.9%. While the good category is 37.7%, and the less category is 11.3%. Based on the age of the majority of respondents with sufficient knowledge as much as 39.6% aged 14-15 years and the minority with less knowledge 1.9% aged 12-13 years. Based on information sources, the majority of respondents obtained information from the mass media as much as 15.1% and the minority 1.9%. From the results of this study, it is hoped that the school and parents of students can play an active role in providing reproductive health, especially menarche.